Fetal and Infancy Growth Pattern, Cord and Early Childhood Plasma Leptin, and Development of Autism Spectrum Disorder in the Boston Birth Cohort. Issue 10 (24th September 2018) - Raghavan, Ramkripa; Zuckerman, Barry; Hong, Xiumei; Wang, Guoying; Ji, Yuelong; Paige, David; DiBari, Jessica; Zhang, Cuilin; Fallin, M. Daniele; Wang, Xiaobin
Abstract : Leptin is a proinflammatory cytokine that plays an important role in energy homeostasis. Emerging evidence suggests that leptin levels are altered in children with autism spectrum disorder (ASD); however, this has not been studied prospectively. Rapid growth during infancy and early childhood has been implicated in ASD, but the evidence is inconsistent. As leptin is involved in growth and is a potential risk factor for ASD, we explored the associations between (a) cord, early childhood leptin and ASD; and (b) birth weight for gestational age, early childhood weight gain, and ASD. We also assessed the mediating role of leptin in the relationship between weight gain during infancy and ASD. This study was conducted in a sample of 822 subjects from the Boston Birth Cohort. ASD was defined from diagnostic codes in electronic medical records. Extremely rapid weight gain during infancy was associated with a greater ASD risk and this persisted after adjusting for potential confounders (aOR: 3.11; 95% CI: 1.37, 7.07). Similarly, children that had higher plasma leptin levels, prior to ASD diagnosis, had an increased ASD risk in both unadjusted and adjusted models (aOR: 7.87; 95% CI: 2.06, 30.04). Further, early childhood leptin indirectly mediated the relationship between rapid weight gain and ASD. No associations were found between birth weight for gestational age, cord leptin and risk of ASD. Our findings provide a basis to further explore whether the combination of early life growth pattern and a biomarker such as leptin can predict ASD earlier. Autism Res 2018, 11: 1416–1431 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Is early life growth and a biomarker leptin related to ASD risk? To answer this question, we followed 822 children from birth and found that those who gained weight very quickly in infancy, had higher leptin levels in early childhood, had a greater chance of later ASD diagnosis. More research is needed to see if infant's weight gain pattern along with a biomarker (such as leptin) can be used to identify children with ASD sooner.